STRATEGI KOMUNIKASI MASYARAKAT DALAM PENGEMBANGAN OBJEK WISATA UNGGULAN PANTAI TANJUNG AMBAT DI KECAMATAN BURU KARIMUN - Iswanti, Desi; Salam, Noor Efni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Buru District has 7 tourist destinations, one of the leading destinations is Tanjung Beach. However, in attracting tourist visitors, an effective communication strategy is needed to create tourist attractions in developing tourist attractions. The purpose of this research is to determine communicator strategies, messages, media channels, and audience determination in developing the superior tourist attraction of Tanjung Ambat Beach. This research method uses a qualitative approach. The subjects in this research consist of seven research subjects as informants using purposive techniques. Data collection techniques are through observation, interviews and documentation. The data analysis technique uses the Miles and Hubermen interactive model. The results of this research show that communication strategies are based on the four elements of Lasswell's communication model. Communicator by conveying messages to the audience. The message was conveyed via the Instagram social media channel with the tag line "Come on holiday to Tanjung Ambat Beach". The media strategy used by social media Instagram and Facebook is very effective in promoting tourist destinations. As well as determining the benefits of collaborating with community leaders and youth in holding events to increase tourist visits. Keywords: Communication Strategy, Tourist Attraction Development, Featured Tourism, Communication Elements, Tourism Village.